PENGARUH UMUR TELUR TETAS PERSILANGAN ITIK TEGAL DAN MOJOSARI DENGAN PENETASAN KOMBINASI TERHADAP FERTILITAS DAN DAYA - Ressi Septika, Elda; Septinova, Dian; Nova, Khaira (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
Hatchery can be done naturally and artificially and or by combining both of the ways. In hatchery,hatch egg age is one of factors which influences fertility, hatchability, hatch loss, and hatchweight. The aims of this study were: 1) to know the effect of hatched egg age of tegal andmojosari duck crossing with combination hatching on fertility, hatch loss, hatchability, and hatchweight; 2) to know the best hatched egg age of hatched egg of tegal and mojosari duck crossingwith combination hatching on fertility, hatch loss, hatchability, and hatch weight. This study usedCompletely Randomized Design with three treatments of hatched egg age (1, 4, and 7 days) and 6replications. The result of this study showed that hatched egg age was significantly different(P<0,05) on hatched egg age (1, 4, and 7 days) and not significantly different (P>0,05) on hatchloss, hatchability, and hatch weight. The the best fertility of hatched egg of 1 day old was 93,75%,even the hatched egg of 4 days old was 83,33%, and the hatched egg of 7 days old was 72,92%.